Oscillating grid mesocosm for studying oxygen dynamics under controlled unsteady turbulence. (23rd September 2015) - Lucas, Sabrina; Moulin, Frédéric; Guizien, Katell
Abstract: In shallow environments, common unsteady flows, such as tides, waves or wind‐driven currents modulate the diffusive boundary layer thickness that controls the exchange of electron acceptors for mineralization and oxidation processes in surficial sediment. This study demonstrated the ability of an oscillating grid mesocosm to (1) produce homogenous turbulence at the sediment‐water interface of multiple sediment cores (between‐core variability < within core variability; 16% on average); (2) simulate diffusive boundary layer thickness dynamics on different timescales by easy control of turbulence intensity and (3) study transient oxygen dynamics of organic matter mineralization under varying turbulent conditions. The relationship between turbulence intensity and oxygen diffusive boundary layer thickness, and oxygen penetration depth in the sediment was investigated with different organic matter enrichments and sediment permeability. Oxygen diffusive boundary layer thickness decreased linearly as U RMS increased. Oxygen penetration depth increased with turbulence intensity, and converging to an upper limit with a larger value for low (3.28 mm ± 5.8%) than for high (1.77 mm ± 11.8%) organic matter content in muddy sediment. In sandy sediment, advective flows and resuspension led to a continuous increase of oxygen penetration depth with turbulence intensity, up to 13.2 mm ± 19% for turbulent velocities of 9.6 cm s −1 . This mesocosm device will enable the experimental study of microbial dynamics under transient oxygen dynamics, to improve early diagenesis modeling under unsteady flows.